(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Computed tomography technology uses an electromagnetic radiation source or particulate radiation source, to analyze / study different samples that can range from living organisms to the most diverse objects (rocks, phantoms, etc.). The use of the radioactive materials may cause harm to the operator if he is exposed to the source of radiation, so aiming at the safety of the operator, the objective of this work is to develop an Internet of Things automation system for the opening of the Industrial Process Tomography source port for industrial tomography applications. Thus, this system can drive the stepper motors through this platform can be opened at a safe distance to the operator, avoiding the operator to take radiation dose to perform this operation. For the IPT project, five source ports were made so that each was positioned diametrically opposite each array of detectors. In this project we used 192Ir sources that have activity of 18,500 MBq and that were produced in the reactor IEA-R1, from the neutron bombardment of the pellet containing stable isotope 191Ir. The main characteristics of 192Ir are: half-life of 74.2 days; radiation energy from 0.13 to 0.65 MeV. For the safety of the operator during the opening of the sources, an automated opening system with IoT that can be activated with software installed on the tomography or by a smartphone application by the MQTT protocol, which makes it possible to be monitored in real time at long distance showing the opening and closing status of each source port.